(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article discusses the key problems affecting the effectiveness of language teaching. The causes of key problems related to teaching are identified, the main difficulties in teaching Russian in a foreign language classroom are identified.